Dielectric properties of TlIn(S₁-xSex)₂ polycrystals near phase transitions - Rosul, R.R.; Guranich, P.P.; Gomonnai, O.O.; Slivka, A.G.; Rigan, M.Yu.; Rubish, V.M.; Guranich, O.G.; Gomonnai, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Studies of polycrystalline TlIn(S₁-xSex)₂ samples under hydrostatic pressure
were performed. Determined in this work were pressure coefficients near temperatures of
ε(T) anomalies. Based on studying the temperature dependences of dielectric permittivity
values for various hydrostatic pressures, (р, Т) phase diagram was built. Phase
transformations are found in the pressure range of p > 550 MPa.